Government of India a Study of the Lok Karya Kshetras of the Bharat Sevak Samaj - Planning Commission (Planning Commission, 1960)
The Public Cooperation Division of the Planning Commission has been giving grants to Bharat Sevak Samaj, a non-polilical voluntary organisation for running 50 Lok Katya Kshetras, mostly located in rural areas. The scheme is intended to secure public participation in various development programmes in the rural sector, both in areas covered by the community development programme and outside. The Division requested the Programme Evaluation Organisation to undertake an immediate evaluation of some Lok Karya Kshetras, and submit a report by the end of February 1960, so that, bused on the results of the evaluation, suitable modifications might be introduced in the next year's programme. The period was later extended to the end of March 1960.
Programme Evaluation Organisation Planning Commission